2019
DOI: 10.1182/blood-2019-123655
|View full text |Cite
|
Sign up to set email alerts
|

Luspatercept Significantly Reduces Red Blood Cell (RBC) Transfusion Burden, Regardless of Gene Mutation Frequency, Spectrum, and Prognostic Significance, Among Patients (Pts) with LR-MDS Enrolled in the MEDALIST Trial

Abstract: Background: Luspatercept is a first-in-class erythroid maturation agent that binds TGF-β superfamily ligands to reduce aberrant Smad2/3 signaling and enhance late-stage erythropoiesis. The phase 3 MEDALIST trial evaluated luspatercept in pts with RBC transfusion-dependent, IPSS-R-defined very low-, low-, and intermediate-risk MDS with ring sideroblasts (RS+) who were refractory, intolerant, or ineligible to receive erythropoiesis-stimulating agents. This study explored associations of gene mutations, as analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 20 Furthermore, the MEDALIST Trial of Luspatercept did not demonstrate that Luspatercept significantly increased the clonal evolution of the gene mutation. 21 Consequently, the reasons for clonal evolution remain unclear, and the consequence of emerging mutations in the ASXL1 gene should be monitored closely.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Furthermore, the MEDALIST Trial of Luspatercept did not demonstrate that Luspatercept significantly increased the clonal evolution of the gene mutation. 21 Consequently, the reasons for clonal evolution remain unclear, and the consequence of emerging mutations in the ASXL1 gene should be monitored closely.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of RBC-TI for ≥8 weeks was reached by 38% in the luspatercept group and 13% with placebo ( p < 0.001), with an overall favorable safety profile [ 7 ]. Subgroup analyses of the MEDALIST trial showed that RBC-TI was achieved independent of co-mutations (including high-risk mutations), did not impact quality of life, had comparable efficacy in patients with MDS/MPN-RS-T, and appeared to yield improvements in platelet (HI-P) and neutrophil counts (HI-N) [ 53 , 54 , 55 , 56 ]. Based on those results, luspatercept has been approved by the United States Food and Drug Administration for ESA-refractory, transfusion-dependent patients with MDS with ring sideroblasts or MDS/MPN-RS-T.…”
Section: Treatment Algorithm For Mdsmentioning
confidence: 99%